Endorphin responses to stress induced by competitive swimming event - Carrasco, L.; Villaverde, C.; Oltras, C. M. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of the present study was to investigate the changes in endorphins (END) induced by swimming competitive practice. Methods: Twenty-three males, (13 trained swimmers [experimental group] and 10 sedentary and healthy students [age-matched comparison group]) took part in this investigation. The swimmers were assessed at 3 points: basal conditions, pre- and postswimming competition (100 m freestyle), whereas subjects from the control group only undertook the basal trial. The variables analysed were anxiety level, plasma END and lactate concentrations. Results: o statistical differences were observed in END basal levels between groups. An evident END response to precompetition psychological stress was observed in the experimental group, since the plasma END concentration rose from 36.3±2.9 pg/mL (basal conditions) to 51.8±3.2 pg/mL (P=0.05). The END response to the competitive effort produced a remarkable increase in its plasma concentration (128.6±18.1 pg/mL), showed statistical differences from precompetition (P£0.01) and from basal conditions (P£0.001). A significant rise in plasma lactate levels just at the end of the effort was found, although it did not correlate with END levels in the same situation. Conclusion: Swimming competition (short-term maximal type of effort) induces a psychological and physiological stress, which stimulates the secretion of END. END are secreted to counter the negative effects of competitive stress, although more research is needed to accurate the relationship between END and anxiety levels during exercise.